Structural similarity of the covalent complexes formed between the serpin plasminogen activator inhibitor-1 and the arginine-specific proteinases trypsin, LMW u-PA, HMW u-PA, and t-PA: Use of site-specific fluorescent probes of local environment - Backovic, Marija (Cold Spring Harbor Laboratory Press, 2002)
We have used two fluorescent probes, NBD and dansyl, attached site-specifically to the serpin plasminogen activator inhibitor-1 (PAI-1) to address the question of whether a common mechanism of proteinase translocation and full insertion of the reactive center loop is used by PAI-1 when it forms covalent SDS-stable complexes with four arginine-specific proteinases, which differ markedly in size and domain composition. Single-cysteine residues were incorporated at position 119 or 302 as sites for specific reporter labeling. These are positions ∼30 Å apart that allow discrimination between different types of complex structure. Fluorescent derivatives were prepared for each of these variants using both NBD and dansyl as reporters of local perturbations. Spectra of native and cleaved forms also allowed discrimination between direct proteinase-induced changes and effects solely due to conformational change within the serpin. Covalent complexes of these derivatized PAI-1 species were made with the proteinases trypsin, LMW u-PA, HMW u-PA, and t-PA. Whereas only minor perturbations of either NBD and dansyl were found for almost all complexes when label was at position 119, major perturbations in both wavelength maximum (blue shifts) and quantum yield (both increases and decreases) were found for all complexes for both NBD and dansyl at position 302. This is consistent with all four complexes having similar location of the proteinase catalytic domain and hence with all four using the same mechanism of full-loop insertion with consequent distortion of the proteinase wedged in at the bottom of the serpin.